2012
DOI: 10.1002/marc.201200594
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐Induced Stabilization of Crystals in Shape Memory Natural Rubber

Abstract: In contrast to all known shape memory polymers, the melting temperature of crystals in shape memory natural rubber (SMNR) can be greatly manipulated by the application of external mechanical stress. As shown previously, stress perpendicular to the prior programming direction decreases the melting temperature by up to 40 K. In this study, we investigated the influence of mechanical stress parallel to prior stretching direction during programming on the stability of the elongation-stabilizing crystals. It was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 31 publications
6
71
0
1
Order By: Relevance
“…[ 19 ] Particularly interesting are polymer networks that not only respond to but also memorize an environmental signal. [ 22,23 ] Further, programmed SMNR strongly responds to liquids and gases by resuming its original shape. We hypothesize that this behavior might be found for those semi-crystalline networks where the change of the amorphous phase has a signifi cant impact on the stability of the crystals.…”
Section: Doi: 101002/adma201305698mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 19 ] Particularly interesting are polymer networks that not only respond to but also memorize an environmental signal. [ 22,23 ] Further, programmed SMNR strongly responds to liquids and gases by resuming its original shape. We hypothesize that this behavior might be found for those semi-crystalline networks where the change of the amorphous phase has a signifi cant impact on the stability of the crystals.…”
Section: Doi: 101002/adma201305698mentioning
confidence: 99%
“…To this end an experiment similar to that above was performed with temperature cycles instead of solvent gas pressure cycles (curves are given in the Supporting Information in Figure S3); we found that the stressanswer of constrained SMNR is indeed dependent on temperature similar to solvent gas. [ 22 ] Furthermore, an irreversible stress-answer Δ σ irr remains after cooling to room temperature. [ 22 ] Furthermore, an irreversible stress-answer Δ σ irr remains after cooling to room temperature.…”
Section: Doi: 101002/adma201305698mentioning
confidence: 99%
“…Secondly, SMNR is the first example of a semi‐crystalline SMP with a significantly tunable trigger temperature 23. Thirdly, even after programming the trigger temperature can be adjusted by mechanically manipulating the stress transverse [stress‐induced melting (SIM)]24 and parallel [stress‐induced stabilizing (SIS)]25 to the elongation‐stabilizing direction. Finally, SMNRs have the capability to store extremely large strains of up to 1000% 23.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4,11,13 ] Furthermore, a high recovery ratio is required to reuse x-PVDF for many shape-memory cycles. [ 16 ] As known from the literature, [ 4,11,13 ] which deals with stretching and rolling of non-x-PVDF, the β-phase content F (β) increases with increasing drawing ratio, while the recovery ratio may decrease as a result from the increasing damage of the sample during rolling. For this reason we investigated the optimal operating point to achieve the highest β-phase content at maximal shape recovery.…”
Section: Resultsmentioning
confidence: 99%